How the mighty fall and why some companies never give in - Collins, Jim. (New York HarperCollins Publishers, 2009)
Discusses signs pointing toward the decline of a business, how far the decline can proceed before failure becomes inevitable, and crucial steps companies can take to reverse course.
Includes bibliographical references (p. [183]-211) and index.
Keywords: Business failures